Standardization of Khadradi Yoga Churna, Mentioned in Sahasra Yogam with Physicochemical and Phytochemical Analysis - Kumara, SMPPS; Jayawardhane, NDN; Jayasuriya, HSV; Chathurika, PKD (International Research Journal of Ayurveda & Yoga, 2025)
Standardization of the herbal preparation is the process of standardizing the quality, consistency, and efficacy of products, aiming to evaluate their therapeutic properties. Analyzing the composition of herbal formulations is crucial for evaluating the quality, purity, safety, and effectiveness of drugs, as determined by the levels of their active ingredients. The current study aimed to establish a comprehensive pharmaceutical and analytical profile of the Ayurvedic poly-herbal Khadiradi Yoga churna, as described in Sahasra Yogam which contain 05 herbal ingredients. Raw material identification done and preparation of medicine was done according to authentic text. Organoleptic evaluation, physicochemical analysis, phytochemical analysis, Chromatographic tests, Heavy metal test, Microbial test were conducted according to Ayurveda Pharmacopeia of India (API) guidelines. Under quality and pharmacological significance, organoleptic evaluation showed traditional sensory attributes (color, odor, and taste). And under physicochemical key parameters; pH, moisture content, and total ash counts, extractive values tests were conducted and results align with API standards. glycosides, saponins, and phenolic compounds were identified as dominant compounds of the final product. TLC and HPTLC fingerprinting confirmed the presence of the main 06 ingredients, validating traditional composition. Absence of pathogens such as E. coli, Salmonella, comply with international standards and reflecting adherence to GMP. A critical safety concern was identified in heavy metal tests, regarding mercury contamination (Hg) 3.4 mg/kg) which is exceeding API acceptance limits (≤1mg/kg). Based on final results, while the Khadiradi yoga churna demonstrates and fulfil excellent phytochemical and microbial quality parameters, Hg contamination overshadows its therapeutic potential. Further market analysis for ingredients, environmental contamination analyses or analysis of manufacturing procedures should be conducted to identify root cause for high mercury contamination.